P039 A novel mean disease alleviation outcome measure in the management of adult obstructive sleep apnoea. (9th November 2022) - Every, J; Sideris, A; Do, T; Jones, A; Weaver, E; Mackay, S
Abstract: Introduction: Current methods assessing device and surgical treatment efficacy for OSA, such as apnoea hypopnea index (AHI), do not factor in compliance. Clinical effectiveness may be better represented when long-term compliance is incorporated into a mean disease alleviation score (MDA). Here, MDA scores between surgery and device are compared in a high-volume adult OSA clinic. Methods: Three hundred and forty-five patients seen over a 13-year period in a high-volume adult OSA clinic staffed by an experienced sleep-trained otolaryngologist and sleep physician were included. Patients were managed with device (Continuous Positive Airway Pressure (CPAP), Mandibular Advancement Splint (MAS) or underwent multilevel airway surgery. Mean disease alleviation was calculated as the product of therapeutic efficacy (change in AHI) and adjusted compliance. Surgical compliance was assumed as one hundred percent. Cardinality matching was utilised to account for differences in patient and disease factors between subgroups. Results: Surgically treated patients demonstrated higher MDA than device users (67.3 ± 29.9% vs. 59.4 ± 31.1%, p=0.039), despite higher therapeutic efficacy seen in device users (85.0±24.4% vs. 67.0±29.9%, p<0.001). Surgical patients were younger, had lower comorbidity scores, lower BMI, and suffered worse daytime sleepiness than device users. Cardinality matching for these factors demonstrated similar mean MDA between groups (66% vs 58%, p=0.11). Device users had to utilise >8hrs per night of compliant use to reach a similar MDA to matched surgical patients. Discussion: In Adult OSA patients with less-than-ideal CPAP compliance, multilevel airway surgery is an equivalent and effective alternative, based on novel MDA measures.